Characteristics and Stability of Mercury Vapor Adsorption over Two Kinds of Modified Semicoke - Zhang Huawei; Liu Xiuli; Wang Li; Liang Peng (The Scientific World Journal)
In an attempt to produce effective and lower price gaseous Hg0 adsorbents, two methods of HCl and KMnO4/heat treatment were used respectively for the surface modification of liginite semicoke from inner Mongolia. The different effects of modification process on the surface physical and chemical properties were analyzed. The characteristics and stability of mercury vapor adsorption over two kinds of modified semicoke were investigated. The results indicated that modification process caused lower micropore quantity and volume capacity of semicoke; the C-Cl functional groups, C=O bond and delocalized electron π on the surface of Cl-SC, the amorphous higher valency Mnx+, and O=C–OH functional groups on the surface of Mn-H-SC were the active sites for oxidation and adsorption of gaseous Hg0. Modification process led to higher mercury removal efficiency of semicoke at 140°C and reduced the stability of adsorbed mercury of semicoke in simulated water circumstance simultaneously.